Cost effectiveness of chest pain unit care in the NHS - Wailoo Allan; Goodacre Steve; Oluboyede Yemi (BMC, 2008)
Abstract Background Acute chest pain is responsible for approximately 700,000 patient attendances per year at emergency departments in England and Wales. A single centre study of selected patients suggested that chest pain unit (CPU) care could be less costly and more effective than routine care for these patients, although a more recent multi-centre study cast doubt on the generalisability of these findings. Methods Our economic evaluation involved modelling data from the ESCAPE multi-centre trial along with data from other sources to estimate the comparative costs and effects of CPU versus routine care. Cost effectiveness ratios (cost per QALY) were generated from our model. Results We found that CPU compared to routine care resulted in a non-significant increase in effectiveness of 0.0075 QALYs per patient and a non-significant cost decrease of £32 per patient and thus a negative incremental cost effectiveness ratio. If we are willing to pay £20,000 for an additional QALY then there is a 70% probability that CPU care will be considered cost-effective. Conclusion Our analysis shows that CPU care is likely to be slightly more effective and less expensive than routine care, however, these estimates are surrounded by a substantial amount of uncertainty. We cannot reliably conclude that establishing CPU care will represent a cost-effective use of health service resources given the substantial amount of investment it would require.